2019
DOI: 10.1038/s41598-019-51367-7
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating Apolipoprotein L1 is associated with insulin resistance-induced abnormal lipid metabolism

Abstract: Circulating ApolipoproteinL1 (ApoL1) is a component of pre-β-high-density lipoprotein (HDL), however little is known about the relationship of ApoL1 with cardiometabolic factors. Considering previous studies reporting the correlation of ApoL1 to triglyceride, we have hypothesized that ApoL1 associates with insulin-related metabolism. The current study examined their associations in 126 non-diabetic subjects and 36 patients with type 2 diabetes (T2DM). Non-diabetic subjects demonstrated triglyceride (standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…It should be noted, however, that we were not able to discriminate the multiple isoforms of apoJ in the present study. ApoL1 also circulates primarily as a component of HDL [ 38 ]. Its plasma levels are correlated with plasma TG [ 39 ], a finding we also observed in our study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, however, that we were not able to discriminate the multiple isoforms of apoJ in the present study. ApoL1 also circulates primarily as a component of HDL [ 38 ]. Its plasma levels are correlated with plasma TG [ 39 ], a finding we also observed in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…Its plasma levels are correlated with plasma TG [ 39 ], a finding we also observed in our study population. The plasma levels of apoL1 have been reported to be increased in patients with metabolic syndrome, and an in vitro study has demonstrated that the insulin signaling pathway regulates both the synthesis and the secretion of apoL1 in hepatocytes [ 38 ]. In agreement with previous findings [ 38 ], we found a significant and positive correlation between apoL1 and HOMA-IR as well as an inverse correlation with plasma adiponectin, reinforcing its potential role in insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…8,13,22,23 Although we cannot exclude the possibility that ER APOL1 "drowns out" the signal in other compartments, we suspect that the far more abundant APOL2 and/or suboptimal staining procedures, epitope tags, transfection artifacts, or different cell types may have contributed to previously published results. At least some of the APOL1 within the ER cisternae is adjacent to (although not specifically enriched in) the MAM, a subdomain of the ER associated with lipid synthesis and ER stress signaling, 43 which is interesting because APOL1 has been reported to affect lipid metabolism, 47 reverse cholesterol efflux, 16 and ER stress. 21,28 Because acidic pH is required for membrane insertion of APOL1, [49][50][51] we expected APOL1 to be soluble in the neutral 52 ER lumen.…”
Section: Discussionmentioning
confidence: 99%
“…The blood cholesterol concentration is mainly dependent on the production, absorption, and catabolism of cholesterol in the liver and intestinal tract [ 20 ]. The measurement of TC content is important as an index of abnormal lipid metabolism in the body [ 21 ]. In addition, as the degree of obesity increased, the TC content increased, and serum TC content was significant for obesity.…”
Section: Resultsmentioning
confidence: 99%